Bahasa Ruang Publik Lembaga Pemerintah di Kepulauan Riau - Tasliati - (Badan Perencanaan, Penelitian dan Pengembangan Pemerintah Provinsi Kepulauan Riau, 2024)
Writings in public spaces not only function as a tool for information but also as a means to represent the linguistic attitude of their creators. If created and published by government institutions, the linguistic attitude of the institution will be reflected. In essence, government institutions can serve as examples in the application of language rules in public spaces, especially in the Riau Islands, which has a strong historical connection to the birth of the Indonesian language. Therefore, this study aims to describe the language used in the public spaces of government institutions in the Riau Islands. Data were collected using the